2022
DOI: 10.1021/acsomega.2c03779
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Enzyme Inhibition Properties of 1,2,4-Triazole Bearing Azinane Analogues

Abstract: Considering the importance of acetylcholine esterase (AChE, BchE) and α-glucosidase in the treatment of Alzheimer’s disease and diabetes mellitus, the synthesis of novel azinane triazole-based derivatives as effective acetylcholinesterase (AchE), α-glucosidase, urease, lipoxygenase (LOX), and butyrylcholinesterase (BChE) inhibitors is described. Azinane analogue ( 2 ) was merged with 1,2,4-triazole to acquire 1-(4-toluenesulfonyl)-4-(3-mercapto-4-methyl-4 H -1,2,4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…[63] As quoted by Ayse Tan in his research, the triazole derivatives appreciably interacted in the active site of XO with various pi-pi interactions and hydrophobic interactions. It has been seen from the extensive literature survey that the triazole ring with certain modifications has been widely studied for the inhibition of various enzymes such as carbonic anhydrase, [64] XO, [65] urease, [66] acetylcholinesterase, [67] butyrylcholinesterase, [68] cyclooxygenase-2, [69] and 15-lipooxygenase. [70] In 2016, Ailong Shi et al, designed and synthesized a series of 2phenyl-5-methyl-2H-1,2,3-triazole-4-carboxylic acid/carbohydrazide derivatives as potent XO inhibitors for the treatment of gout.…”
Section: Significance Of 123-triazole Scaffold As Potent Xo Inhibitorsmentioning
confidence: 99%
“…[63] As quoted by Ayse Tan in his research, the triazole derivatives appreciably interacted in the active site of XO with various pi-pi interactions and hydrophobic interactions. It has been seen from the extensive literature survey that the triazole ring with certain modifications has been widely studied for the inhibition of various enzymes such as carbonic anhydrase, [64] XO, [65] urease, [66] acetylcholinesterase, [67] butyrylcholinesterase, [68] cyclooxygenase-2, [69] and 15-lipooxygenase. [70] In 2016, Ailong Shi et al, designed and synthesized a series of 2phenyl-5-methyl-2H-1,2,3-triazole-4-carboxylic acid/carbohydrazide derivatives as potent XO inhibitors for the treatment of gout.…”
Section: Significance Of 123-triazole Scaffold As Potent Xo Inhibitorsmentioning
confidence: 99%
“…Asif et al [105] . synthesized azinane containing 1,2,4‐triazoles and assessed for their antiurease potential.…”
Section: Triazoles As Urease Inhibitorsmentioning
confidence: 99%
“…Asif et al [105] synthesized azinane containing 1,2,4-triazoles and assessed for their antiurease potential. Outcomes revealed that only derivatives 43 c, 43 d, 43 i, 43 j, 43 k, and 43 m endured potency against urease enzyme, while compounds 43 d and 43 m displayed effective inhibition; 98.22 and 98.65 %, respectively in comparison to standard thiourea (98.28 % inhibition).…”
Section: Chemistryselectmentioning
confidence: 99%
“…Asif et al [ 81 ] synthesized 1,2,4‐triazole bearing azinane hybrids and evaluated them against urease. The SAR study of compound 170a (IC 50 = 14.29 μM) bearing CH 3 in 3‐ and 5‐positions on the phenyl ring is stronger than thiourea (IC 50 = 21.37 μM).…”
Section: Triazolesmentioning
confidence: 99%